Transforming Catechesis with Multimedia: Enhancing Quality and Engagement in Religious Education - Tarihoran, Emmeria; Firmanto, Antonius Denny (Yayasan Ilomata, 2024)
Religious teachings are an urgent part of education to shape one's character and morals. In the digital era, multimedia is utilized as an effective tool to enhance the quality of teaching and make learning more engaging. This article aims to discuss the implementation of multimedia as a teaching aid in religious teaching in the digital age. The research method used is literature study by collecting data from relevant and up-to-date literature. Through a literature study, the author introduces the concept of multimedia and its benefits in teaching religious. In the context of multimedia in religious education, researchers employ content analysis to examine and interpret the content of multimedia materials used in teaching. This analysis involve identifying recurring themes, analyzing the alignment of multimedia content with religious teachings, and evaluating the effectiveness of multimedia elements (e.g., visuals, audio, interactivity) in conveying religious concepts. The results indicate that multimedia can enhance the teacher teaching process and improve the learning experience for participants. However, the use of multimedia in catechesis also presents challenges, such as technical issues and excessive usage. The author suggests a selective and thoughtful approach when utilizing multimedia in catechesis. This article is helpful for religious educators and catechists in understanding the significance of multimedia use in religious education in the digital age and implementing it effectively. In conclusion, this article emphasizes the imperative role of spiritual teachings in education for shaping individuals' character and morals, underscoring the significance of prudently integrating multimedia technology within religious learning.